2022
DOI: 10.1021/acsomega.2c00204
|View full text |Cite
|
Sign up to set email alerts
|

Quenching the Macroporous Collapse of Polyelectrolyte Multilayer Films for Repeated Drug Loading

Abstract: Macroporous structures can be developed within polyelectrolyte multilayer films for efficient drug loading, but these structures tend to collapse or fracture during conventional drying procedures. Herein, a facile dehydrating method for macroporous polyelectrolyte multilayer films is proposed using solvent exchange to ethanol and then spontaneous evaporation. During these processes, the collapse of the macroporous structures can be effectively avoided, which can be ascribed to a combined effect of two factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…In contrast to water which is capable of disrupting ionic bonds between polyelectrolyte chains and contributing to yield benign plasticizing effect to PEC materials, ethanol may hardly serve as a plasticizer for PEC materials owing to its relatively low dielectric constant as well as its weak impact on the dissociation of the interchain ionic bonds. For ease of comparison, we measured Young’s moduli of a PEI/PAA film when it was hydrated under water and incubated in a bath of ethanol, respectively. It was found that the result of the former is much lower than that of the latter, i.e., 1.41 versus 1342.5 MPa (Figures C and S13), indicating the huge difference between water and ethanol in aspects of plasticizing PEC materials.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to water which is capable of disrupting ionic bonds between polyelectrolyte chains and contributing to yield benign plasticizing effect to PEC materials, ethanol may hardly serve as a plasticizer for PEC materials owing to its relatively low dielectric constant as well as its weak impact on the dissociation of the interchain ionic bonds. For ease of comparison, we measured Young’s moduli of a PEI/PAA film when it was hydrated under water and incubated in a bath of ethanol, respectively. It was found that the result of the former is much lower than that of the latter, i.e., 1.41 versus 1342.5 MPa (Figures C and S13), indicating the huge difference between water and ethanol in aspects of plasticizing PEC materials.…”
Section: Resultsmentioning
confidence: 99%